The feasibility of using the application developed to operationalize the Global Diet Quality Score in Ethiopia - Yonas Taffesse Asrat; Mourad Moursi; Marieke Vossenaar; Megan Deitchler; Abdulaziz Omare (BMC Nutrition)
Abstract Background The Global Diet Quality Score (GDQS) application is an electronic data collection tool developed to provide a standard, easy-to-use method for collecting low-cost, time-relevant data on diet quality. Objective To assess the feasibility and ease-of-use of the GDQS application and associated set of 3D cubes used as visual aids to assist the respondent with estimating amounts consumed at the food group level. Methods The study was conducted in August 2021 in two regions of Ethiopia with varied dietary practices. Face-to-face interviews were conducted in Amharic and Somali by 10 enumerators among 120 women to collect dietary data using the GDQS application. Feedback on each completed interview was collected from both the respondent and enumerator. Enumerators also participated in focus group discussions. Results Enumerators rated the GDQS application as easy to use after 85.8% of the interviews completed. They identified the automatic provision of food-specific probes to guide the interview, the automatic classification of reported foods, beverages, and ingredients into the corresponding GDQS food groups, and the ability to work offline as the main advantages of the application. Most respondents (78.3%) did not find it difficult to choose the cube that corresponded to the amount of each food group they reported consuming. Respondents’ feedback on the open recall of all foods, beverages and mixed dishes consumed the previous day and the use of 3D cubes was mostly positive. Conclusion The results suggest that the GDQS application and cubes were easy to use and feasible for collecting data on diet quality in a low-income country setting.